1977
DOI: 10.1016/s0022-5320(77)90025-9
|View full text |Cite
|
Sign up to set email alerts
|

Collagen structure: Evidence for a helical organization of the collagen fibril

Abstract: The collagen fibrils of human or guinea pig dermis when exposed to the denaturing agents, urea or guanidine-HC1, dissociated into smaller, disparate subunits, probably aggregates of microfibrils. The process of dissociation demonstrates that the fibrils are assembled helically. Initially, diagonal clefts appear on the surface of the fibril. These clefts are surface manifestations of a spirally oriented, internal space. Continued exposure to these denaturants resulted in progressive dissociation of the fibril i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…The direction oftilt is fixed relative to the radially oriented 3.8-nm spacing. Therefore, the molecules appear to follow a "helical" path around the fibril (25,(27)(28)(29)(30)(31)(32)(33) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direction oftilt is fixed relative to the radially oriented 3.8-nm spacing. Therefore, the molecules appear to follow a "helical" path around the fibril (25,(27)(28)(29)(30)(31)(32)(33) …”
Section: Resultsmentioning
confidence: 99%
“…D-periodic filaments of the appropriate width have been observed (26) but, because oftheir unknown depth, unequivocal evidence for the existence of a microfibril is still unavailable, and thus the exact nature of the observed filaments remains obscure. Finally, electron microscopy of freeze-fractured preparations (27)(28)(29)(30)(31) or ultrathin sections of either inertly dehydrated (25) or chemically treated (32,33) tissues indicates a helical filamentous arrangement in collagen fibrils.…”
mentioning
confidence: 99%
“…The analysis of serial sections performed in the present study, showed that the subfibrils present on the surface of thick fibrils have a spiral counterclockwise direction, whose meaning, however, is unknown to us. Spiral arrangement of collagen fibrils has been observed after exposition of tissues to 4 M guanidinium chloride (Marchini et al, 1986) or other dissociative solvents such as 8 M urea (Lillie et al, 1977). The images suggest that the ridges could result, at least in part, from the lateral aggregation of collagen fibrils on already formed collagen fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with disruption agents such as 8 M urea has been recommended for exposing collagen epitopes, (Fleischmajer et al, 1990a). According to Lillie et al (1977), the urea disrupts collagen fibrils by breaking their hydrogen bonds. The degree of dissociation depends on intra-and intermolecular cross-links and is usually extensive in embryonic skin and to varying degrees in the adult skin.…”
Section: Discussionmentioning
confidence: 99%